French Tourism and Hospitality Teaching At College of Tourism: How does it work ? - Wahyu Indrayatti; Ida Zulaeha; Tommi Yuniawan; Diah Vivi Widayanti (Universitas Negeri Semarang, 2023)
French is one of the foreign languages studied by students from the College of Tourism (STP) to support the professionalism of prospective workers in tourism and hospitality. This study aims to describe the French Tourism and Hospitality courses at the College of Tourism, covering four aspects of perception, lecture motivation, and evaluation. The data collection technique in this study was a questionnaire. The discussion concluded that implementing FSP lectures at the College of Tourism had not fulfilled the provisions in the performance of foreign language learning with professional goals. This statement is known from the learning objectives that have not led to FSP learning, learning materials in which general French still dominates, learning activities that have not shown professional competence developers in the field of Tourism and Hospitality, and the assessments carried out have not touched on the competencies that students should have achieved. The benefits of research can be used as a reference in improving the curriculum and process of French language lectures at the College of Tourism.